Preliminary Studies on Anticoagulation and Antiplatelet Activities of Plinia cauliflora (Mart.) Kausel Leaves Extract - Filipe Tanelli, Thaís Gascón Belardo, Carlos Henrique Foncesca Peiro, Robson Miranda da Gama, Fernando Luiz Affonso Fonseca, José Armando-Junior (Journal of Applied Pharmaceutical Science, 2017)
The objective of this study was to evaluate the effect of aqueous extracts of Plinia cauliflora (DC.) Kausel leaves in different concentrations (0.5 to 10.0% (w/v)), on the hemostasis through changes in platelet aggregation and blood coagulation. Has been assessed by phytochemical screening (total phenols; tannins; flavonoids; alkaloids and saponins) of Plinia cauliflora (DC.) Kausel leaves using standard methodologies. The human blood by discard sample was used. The coagulation assay was carried out with ‘thromboplastin hemostasis’ for prothrombin time (PT) and activated partial thromboplastin time (aPTT) commercial kit, where platelets were determined by complete blood count (CBC) analyzer. The phytochemical screening showed the presence of total phenols; tannins and flavonoids. In assessing the anticoagulant activity, the aqueous extracts of P. cauliflora (DC.) Kausel leaves in different concentrations (2.0%; 2.5%; 5.0% and 10.0% (w/v) didn't show any coagulation and could not be measured on the analyzer. Hemogram (CBC) of the sample results showed a significant reduction in platelet concentration, especially in aqueous extracts 2.5%, while the other parameters did not seem to be significantly affected. Based on these preliminary results, it can be suggested that the aqueous extract of this species has anticoagulant and antiplatelet activities.
Keywords: Anticoagulant activity, hemostasis, Plinia cauliflora (DC.) Kausel, platelet.